Study on Direct Shear Properties of Cured Loess with Double-poly Material - ZHU Lijun; PEI Xiangjun; ZHANG Xiaochao; REN Tong (Renmin Zhujiang, 2020)
In order to improve the slope erosion in the loess region, this paper conducts a laboratory test to study the curing effect of the dual-poly material on the loess and the mechanical properties of the cured loess under extreme dry and extreme saturated conditions, and adjusts and controls the dry density of the soil (as supplementary measure) to ensure the accuracy of experimental results and correctness of trends. The results show that: the addition of double-poly materials can increase the saturated moisture content of the soil sample, which increases first and then decreases as the density increases;under extreme dry and fully saturated conditions, the cohesion and internal friction angle of cured soil are much larger than those of the uncured soil, the effect of the material on the internal friction angle is most obvious when it is saturated;with consideration of the mechanical properties and comprehensive factors, the performance is optimal with 0.34% material content.